Nutritional Profile of Four Shrub Species, Northeastern Mexico - Dominguez-Gomez, Tilo G.; Gonzalez-Rodriguez, Humberto; Ramirez-Lozano, Roque G.; Cantu-Silva, Israel; Gomez-Meza, Marco V.; Cantu-Ayala, Cesar M.; Alvarado`5, Maria Del S. (International Journal of Bio-resource and Stress Management, 2023)
The aim of this study was to assess the monthly variation in the chemical composition of four native shrubs in northeastern Mexico. Organic matter (OM), acid detergent fiber (ADF) and nitrogen were determined and digestible energy (DE) and insoluble neutral detergent fiber (INDF) were also estimated. Leaves from Acacia amentacea, Parkinsonia texana, Forestiera angustifolia and Celtis pallida were collected during twelve consecutive months (2009) in three county sites (China, Linares and Los Ramones Counties) of the state of Nuevo Leon, Mexico. The OM (total mean= 81%), ADF (22%), N (2.7%), DE (3.0 kcal kg-1 DM) and INDF (30 g kg-1 DM) were significantly different among sites, species and months and the double (month*site, month*species, species*site) and triple interactions (month*site*species) were also significant (p<0.001). In general, Linares site had higher OM, ADF and INDF than the other sites. The China site had the higher N and the DE content was similar among sites. Low content of INDF and FDA and high DE value in C. pallida and P. texana may indicate that these plants are a good food for range ruminants. Conversely, A. amentacea and F. angustifolia had low nutritional value because their high content of ADF, INDF and low DE value.